Case studies on simulations of flow-induced vibrations of a cooled circular cylinder: Incompressible flow solver for moving mesh problem - Chandrakant Sonawane, PhD (Case Studies in Thermal Engineering, 2022)
The paper presents an in-house code developed for simulating incompressible flow involving moving boundaries. The solver is based on Arbitrarily Lagrangian-Eulerian formulation with Harten Lax and van Leer with Contact for artificial compressibility (ALE-HLLC-AC) method. In the finite volume formulation, the moving boundary problem is taken care of by the arbitrarily Lagrangian-Eulerian formulation, where radial basis function-based interpolation is employed to move the meshes. The Harten Lax and van Leer with -Contact scheme developed to evaluate the convective fluxes in artificial compressibility formulation. High order accuracy is achieved over an unstructured data structure by developing solution-dependent weighted least squares-based gradient calculations. Flow-induced vibrations caused due to the cyclic lift forces over a cooled circular cylinder are simulated and compared with available literature results. For flow-induced vibration of circular cylinder: fluid-structure interaction problem, the elastically mounted cylinder wall temperature is maintained lower than the flowing fluid. The cylinder vibrates transverse to the direction of fluid flow, and its oscillating movement is simulated using a numerical mass-spring-damper system. Both heat transfer scenarios, i.e., without gravity and gravity acting against the flow direction, are simulated. The unsteady, laminar, incompressible flow analysis is carried out at Richardson number (−1, 0) for the cooled circular cylinder with various reduced velocities Ur (3–20). Prandtl number and Reynolds number are Pr = 7.1 and Re = 150, with the fixed mass ratio of 2 and zero damping coefficient. The validation of the results is presented in the literature. It has been noticed that the thermal boundary layer affects the fluid characteristics. The vibration of the cylinder reached the highest amplitude of cylinder dimension, more dominantly in the range of reduced velocities (4–15), showing a galloping kind of flow nature.